MUTU GIZI PANGAN, INDEKS MASSA TUBUH DAN KADAR HEMOGLOBIN REMAJA PUTRI DI WILAYAH LOKUS STUNTING DESA SUKAMANTRI KABUPATEN TANGERANG - Hanifah, Luthfi Nur; Nadiyah, Nadiyah; Dewanti, Lintang Purwara; Palupi, Khairizka Citra; Ronitawati, Putri (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: Indonesia faces nutritional problems, including nutritional anemia. One of the most susceptible groups to anemia is teenage girls, as evidenced by the still high prevalence of iron deficiency anemia in teenage girls. The behaviour of teenage girls who consume more vegetable foods than animal proteins affects haemoglobin levels, as well as teenage girls' habits defining body image make them restrict their daily intake of food, thereby causing the teenager to suffer from anemia.Objective: To determine the correlation between the nutrition quality of foods and body mass index (BMI) with haemoglobin levels in teenage girls in the Stunting Locus Area of Sukamantri Village, Tangerang Regency.Methods: Respondents to this study were teenage girls aged 12 to 18 years. The study was conducted in two primary and two secondary schools with a cross-sectional research design. Subjects 141 teenage girls were selected by multistage cluster sampling. Haemoglobin levels were measured using the Mission Hb, weight measurement using digital scales, and height using microtoise food. Nutritional quality was measured using food recall 2x24 hours. Independent variables were the nutritional quality of food and body mass index, and the dependent variable was haemoglobin levels. The bivariate analysis used the Spearman and Pearson correlation test correlation tests.Results: The average haemoglobin level is 13.0 ± 1.40 g/dL. The Z-score ratio is based on BMI-for-age -0.03 ± 1.3 z-score, and the median quality of food nutrition value of food is 62.26±1.19%. There are no significant correlations between the nutritional quality of food, body mass index and haemoglobin levels of teenage girls (p>0.05).Conclusion: The nutritional value of food, body mass index, and haemoglobin levels are not significantly correlated. Keywords: Body Mass Index; Hemoglobin; Nutritional Quality of Food; Teenage Girls ABSTRAKLatar Belakang: Indonesia menghadapi permasalahan gizi, termasuk anemia gizi. Salah satu kelompok yang paling rentan terkena anemia adalah remaja putri, hal ini dibuktikan dengan masih tingginya prevalensi anemia defisiensi besi pada remaja putri. Perilaku remaja putri yang lebih banyak mengonsumsi makanan nabati dibandingkan protein hewani mempengaruhi kadar hemoglobin, begitu pula dengan kebiasaan remaja putri. Penurunan citra tubuh membuat mereka membatasi asupan makanan sehari-hari, sehingga menyebabkan remaja tersebut menderita anemia.Tujuan: Mengetahui hubungan kualitas gizi makanan dan indeks massa tubuh (IMT) dengan kadar hemoglobin pada remaja putri di wilayah Lokus Stunting Desa Sukamantri Kabupaten Tangerang.Metode: Responden penelitian ini adalah remaja perempuan berusia 12 sampai 18 tahun. Penelitian dilakukan di empat sekolah, dua sekolah dasar dan dua sekolah menengah dengan desain penelitian cross-sectional. Sebanyak 141 responden remaja putri yang dipilih secara multistage cluster sampling. Kadar hemoglobin diukur menggunakan Mission Hb, pengukuran berat badan menggunakan timbangan digital dan tinggi badan menggunakan microtoise. Kualitas gizi pangan diukur menggunakan food recall 2x24 jam. Variabel bebas dalam penelitian ini yaitu kualitas gizi makanan dan indeks massa tubuh, sedangkan variabel terikat dalam penelitian ini yaitu kadar hemoglobin. Analisis bivariat menggunakan uji korelasi uji korelasi Spearman dan Pearson.Hasil: Rata-rata kadar hemoglobin 13.0 ± 1.40 g/dL. Rasio z-score berdasarkan BMI untuk usia -0.03 ±1.3 SD dan median kualitas makanan nilai gizi makanan adalah 62.26±1.19% Tidak ada hubungan yang bermakna antara kualitas gizi makanan, indeks massa tubuh dan kadar hemoglobin remaja putri (p>0.05).Simpulan: Nilai gizi makanan, indeks massa tubuh dan kadar hemoglobin tidak berhubungan nyata. Kata Kunci: Indeks Massa Tubuh; Kadar Hemoglobin; Mutu Gizi Pangan; Remaja Putri